Beban Kognitif Siswa menggunakan Asesmen Formatif Berbasis Digital Escape Room pada Situs Web Genially: (Students’ Cognitive Load in Using Digital Escape Room–Based Formative Assessment on the Genially Website) - Nuraida, Indri; Wulan, Ana Ratna (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Biology learning assessments often generate excessive cognitive load because they insufficiently account for students' limited working memory capacity, particularly for complex topics such as viruses. This condition can hinder concept understanding and reduce learning motivation, so a more interactive, process-oriented formative assessment is needed. This study aims to describe students' cognitive load and examine the role of Digital Escape Room (DER)-based formative assessment on the Genially website in managing students' cognitive load in biology learning on virus material. The study used a quantitative descriptive approach with a one-shot case study design. The subjects were grade X students selected through purposive sampling. The instruments consisted of a subjective rating scale questionnaire measuring intrinsic cognitive load (ICL), extraneous cognitive load (ECL), and germane cognitive load (GCL), as well as an open-ended questionnaire exploring students' experiences, obstacles, and expectations. Data were analyzed using descriptive statistics and qualitative analysis. The results show that ECL fell into the lowest category, while GCL fell into the highest category. This pattern, low ECL and high GCL, is consistent with a cognitive load profile that supports the process of understanding the concept of viruses. In addition, students showed a positive response to a more engaging and enjoyable assessment experience, although technical obstacles and time constraints were still found. The implications of this study suggest that DER-based formative assessment on the Genially website has the potential to become an effective, innovative alternative assessment in biology learning. Abstrak. Asesmen pembelajaran biologi sering menimbulkan beban kognitif berlebih karena kurang memperhatikan keterbatasan kapasitas memori kerja siswa, terutama pada materi-materi yang kompleks, seperti virus. Kondisi ini dapat menghambat pemahaman konsep dan menurunkan motivasi belajar, sehingga diperlukan asesmen formatif yang dirancang lebih interaktif dan berorientasi pada proses belajar. Penelitian ini bertujuan untuk mendeskripsikan beban kognitif siswa serta mengkaji peran asesmen formatif berbasis digital escape room. (DER) pada situs web Genially dalam mengelola beban kognitif siswa pada pembelajaran biologi materi virus. Penelitian menggunakan pendekatan deskriptif kuantitatif dengan desain one shot case study. Subjek penelitian adalah siswa kelas X yang dipilih menggunakan teknik purposive sampling. Instrumen penelitian meliputi kuesioner subjective rating scale untuk mengukur intrinsic cognitive load (ICL), extraneous cognitive load (ECL), dan germane cognitive load (GCL), serta angket terbuka untuk menggali pengalaman, kendala, dan harapan siswa. Data dianalisis menggunakan statistik deskriptif dan analisis kualitatif. Hasil penelitian menunjukkan bahwa ECL berada pada kategori paling rendah, sedangkan GCL berada pada kategori paling tinggi. Temuan ini mengindikasikan bahwa asesmen formatif berbasis DER mampu meminimalkan beban kognitif yang tidak relevan dan mendorong usaha kognitif siswa dalam memahami konsep virus. Selain itu, siswa menunjukkan respons positif terhadap pengalaman asesmen yang lebih menarik dan menyenangkan, meskipun masih terdapat kendala teknis dan keterbatasan waktu. Implikasi penelitian ini menunjukkan bahwa asesmen formatif berbasis digital escape room pada situs web Genially berpotensi menjadi alternatif asesmen inovatif yang efektif dalam pembelajaran biologi.